European company law - Vicari, Andrea, 1968- (De Gruyter Studium., 2021)
"The book provides students of European company law courses, scholars and practitioners with an overview. Although company law remains mainly regulated at the level of national laws, it has become important to obtain a systematic view of the main directives in the field of company law, the EU Court of Justice's jurisprudence, the European Model Company Act and the state of implementation of these directives in the member states of the Union. The book therefore contains, in addition to the illustration of the law laid down by EU legislative bodies and the related soft laws, detailed references to the most important domestic legislations and case laws, in order to make them known and usable as much as possible. Moreover, the book allows identifying the most relevant current legislative trends and the main historical reasons for divergences"--